Reseña de Croft, William y Cruse, Alan (2004). Cognitive Linguistics, Cambridge: Cambridge University Press. - Berbeira Gardón, José Luis (Pragmalingüística, 2010)
<!–[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Se trata de una reseña sobre Croft, William y Cruse, Alan (2004). Cognitive Linguistics, Cambridge: Cambridge University Press. ISBN 0 521 66770. 356 págs.